ANALISIS PENGARUH PELATIHAN DAN KEMAMPUAN KERJA GUNA MENINGKATKAN KINERJA KARYAWAN PT. DEWI SRI KECAMATAN WLINGI KAB. BLITAR - Damayanti, Kristya; Sasmito, Aldi (Parsimonia - Jurnal Ekonomi dan Bisnis, 2022)
Research at the coffee plantation company PT. Dewi Sri to find the effect of the training and ability / work skills on employee performance. The methods of collecting data and information through questionnaires and interviews with 67 respondents. The data analysis is descriptive quantitative analysis with validity test, reliability test, classical assumption test (normality, heteroscedasticity, autocorrelation, multicollinearity), multiple linear regression, hypotesis testing (partial test, simultaneous test) using SPSS softwar. The variables are job training and ability / job skills (independent variable), and employee performance (dependent variable). The results of partial test shows the independent variables, that is job training (X1) and work abilities / skills (X2) each have an effect on dependent variables, that is performance (Y). Simultaneous test result show that the independent variable training (X1) and work abilities/skills (X2)have an affect to dependent variable, that’s performance (Y).